THE WAITER AT PRINCESS REATAURANT ALWAYS RESPECTS HIS GUESTS “AS A KING” TO WINNING RESTAURANT BUSINESS IN ASEAN ECONOMY COMMUNITY (AEC) ERA - I Wayan Pugra; Ida Ayu Ketut Sumawidari; I Ketut Redjasa (Institut Pariwisata dan Bisnis Internasional, 2016)
Nowadays is said to be Asean Economy Community (AEC) era. The competition on getting a job in Asean especially in Bali are getting hard and so does in restaurant business competition is getting tighter and tighter. How to winning it ? The answer by Princess Restaurant’s management is “Always respects his guests as “A KING” in Asean Economy Community (AEC) era.This research is aimed to know the daily duties of waiters at Princess Restaurant if they have a specific tricks to winning restaurant business in Asean Economy Community Era.Data of this research are obtained from informants who knows the object of the research such as The Princess Restaurant Manager, Resaturant Captains, Restaurant waiters and bus boys. After that, the data are analyzed descriptively by explaining in detail the data which has been collected to get a clearer understanding.The result of this research showed that the daily duties of waiters at Princess Restaurant always respects his guest as “A KING” in order to winning restaurant business in AEC era.That smart technics by waiters at Princess Restaurant could make most guest who enjoy food and drinks at Princess Restaurant feel happy and satisfied and finally could attract the guest to come again frequently as repeater guests.This waiter’s smart ways, could offer great satisfaction and nice experiences to all guests, and finally could give a positive contribution to economy, social and prosperous happiness to local people who works there.